2015
DOI: 10.4274/uob.352
|View full text |Cite
|
Sign up to set email alerts
|

The Current Radiological Approach to Renal Cell Carcinoma

Abstract: GirişRenal hücreli karsinom (RHK), erişkinlerde sekizinci sıklıkta görülen malignensidir. Klinik olarak flank ağrı, hematüri ya da palpable flank kitle şeklinde ortaya çıkabilir. Ultrason (US), bilgisayarlı tomografi (BT) ve manyetik rezonans görüntüleme (MRG) yöntemlerinin kullanımlarının artması ile rastlantısal olarak saptanan tümörlerde de artış mevcuttur (1). RHK erişkinde primer malign renal neoplazilerin %80-90'ını oluşturmaktadır (2). Heidelberg klasifikasyonuna göre farklı histolojik subtipi (berrak h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In our country, it is reported that the disease is observed in the Black Sea region, some parts of Central Anatolia, and the province of Denizli, with an incidence rate of 3%-80% (1,4,5).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In our country, it is reported that the disease is observed in the Black Sea region, some parts of Central Anatolia, and the province of Denizli, with an incidence rate of 3%-80% (1,4,5).…”
Section: Introductionmentioning
confidence: 88%
“…Primary or secondary copper deficiency in lambs causes enzootic ataxia, characterized by degeneration of the central nervous system and developmental disorders (1,2,3). In our country, it is reported that the disease is observed in the Black Sea region, some parts of Central Anatolia, and the province of Denizli, with an incidence rate of 3%-80% (1,4,5).…”
Section: Introductionmentioning
confidence: 93%